Analisis Pengaruh Economic Value Added (EVA), Debt To Equity Ratio (DER), Return On Asset (ROA), dan Current Ratio (CR) terhadap Return Saham - Muhammad Rois; Pandiya Pandiya; Ni Made Diah K.S (JSHP : Jurnal Sosial Humaniora dan Pendidikan, 2019)
This study aims to examine the significance of the effects of Economic Value Added, Debt to Equity Ratio, Return on Assets, and Current Ratio To stock againts returns in mining sector companies listed in Indonesia Stock Exchange 2013-2017. This study uses secondary data. The samples in this research are determined by purposive sampling technique. The samples used in this research are 6 (six) mining companies listed on Indonesia Stock Exchange. Testing hypothesis by using regression tool of panel data  supported by software eviews 9. Results of F test of  this research show that Economic Value Added (EVA), Debt to Equity Ratio (DER), Return on Asset (ROA), simultaneously have a significant effect against stock returns on the company. The result of t test shows that the Economic Value Added partially does not have a significant effect on stock return, while the Debt to Equity Ratio, Return on Asset, and Current Ratio have significant effect to stock return on mining companies listed in Indonesia Stock Exchange period 2013-2017.